Cross-cultural adaptation of a prenatal counseling questionnaire for congenital heart disease in Brazilian Portuguese - Rocha Amorim, Luciane Alves da; de Morais Almeida, Sophia Livas; Callado, Gustavo Yano; Kovacevic, Alexander; Bär, Stefan; Araujo Júnior, Edward (Pediatric cardiology, 2026)
Congenital heart disease (CHD) is the most common congenital anomaly and a major cause of neonatal morbidity and mortality worldwide. A prenatal diagnosis of CHD is a psychologically distressing event that requires sensitive and effective counseling. However, no validated tool exists in Brazilian Portuguese to assess the quality of counseling provided to families following such diagnosis. To conduct the cross-cultural adaptation and content validation of “Kovacevic Questionnaire” for evaluating parental counseling after prenatal CHD diagnosis into Brazilian Portuguese. This cross-sectional study followed the standardized guidelines for cultural adaptation proposed by Beaton et al. The process included translation, synthesis, back-translation, expert review, pre-testing, and psychometric evaluation. Two Expert Committees assessed semantic, idiomatic, cultural, and conceptual equivalence. Content Validity Index (CVI), Prevalence- and Bias-Adjusted Kappa (PABAK), and Content Validity Coefficient (CVC) were calculated. The adapted instrument was pre-tested with ten pregnant women carrying fetuses diagnosed with CHD. The adaptation process resulted in a culturally relevant and linguistically accurate Brazilian version. Expert agreement was high, with most items achieving CVI and PABAK values close to 1.0 and CVC values ≥ 0.80. Minor linguistic refinements were made for clarity and cultural sensitivity. Pre-test participants rated all items as clear and relevant, with CVI and PABAK equal to 1.00. The Brazilian Portuguese version of “Kovacevic Questionnaire” demonstrated high validity and acceptability. It provides clinicians and researchers with a reliable tool to assess and enhance counseling quality for families facing prenatal CHD diagnoses, particularly in diverse and resource-constrained settings such as the Amazon region.
Gesehen am 23.02.2026